2016
DOI: 10.1177/0733464816649278
|View full text |Cite
|
Sign up to set email alerts
|

Care Challenges in the Bathroom: The Views of Professional Care Providers Working in Clients’ Homes

Abstract: In home care, bathroom activities-particularly bathing and toileting-present a unique set of challenges. In this focus group study, professional home care providers identified factors that increase the danger and difficulty of assisting their clients with bathing and toileting. These included small restrictive spaces, a poor fit between available equipment and the environment, a reliance on manual handling techniques (but insufficient space to use optimal body mechanics), attempts to maintain normalcy, and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 37 publications
(53 reference statements)
0
40
0
Order By: Relevance
“…Assisting with toileting is commonly identified by home care providers and family caregivers as a frequent and physically demanding task (Czuba et al, 2012; Darragh et al, 2015; Katz et al, 1963; King et al, 2018, n.d. ; Owen & Staehler, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Assisting with toileting is commonly identified by home care providers and family caregivers as a frequent and physically demanding task (Czuba et al, 2012; Darragh et al, 2015; Katz et al, 1963; King et al, 2018, n.d. ; Owen & Staehler, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Providing assistance with posterior perineal care led to the highest levels of most calculated risk factors. This task has been described by home care providers as one of the most challenging elements of assisting with toileting (King et al, 2018). In combination with replacing the pants, Hjalmarson's (2014) toileting simulation also found that providing hygienic care was associated with very high frequencies of nonneutral trunk postures.…”
Section: Providing Posterior Perineal Carementioning
confidence: 99%
See 3 more Smart Citations